Impact of concurrent amiodarone treatment on the tolerability and efficacy of carvedilol in patients with chronic heart failure. Issue 5 (1st November 1999) - Macdonald, P S; Keogh, A M; Aboyoun, C; Lund, M; Amor, R; McCaffrey, D
Abstract : OBJECTIVE: To assess the safety and efficacy of carvedilol when administered to heart failure patients already receiving amiodarone. DESIGN: Retrospective analysis of the clinical outcome of 230 patients treated with carvedilol for chronic heart failure, stratified according to whether they were already receiving amiodarone (amiodarone group, 80 patients) or not (non-amiodarone group, 130 patients) at baseline. SETTING: Heart failure clinic at a university affiliated public teaching hospital. MAIN OUTCOME MEASURES: Incidence of adverse events; changes in functional status and echocardiographic dimensions at three months. RESULTS: Adverse reactions to carvedilol occurred in 33 (41%) of the amiodarone group and 43 (29%) of the non-amiodarone group (p = 0.049). Carvedilol was discontinued in 21 (26%) of the amiodarone group and 37 (25%) of the non-amiodarone group (NS). The clinical outcome at three months did not differ significantly between the two groups; 31 (39%) of the amiodarone group improved their New York Heart Association status, 28 (35%) were unchanged, and 21 (26%) deteriorated compared with 67 (45%), 51 (34%), and 32 (21%), respectively, for the non-amiodarone group (NS). Both groups had highly significant decreases in heart rate and left ventricular end systolic dimension, and a significant increase in left ventricular ejection fraction after three months of carvedilol treatment, with no significant differences between the groups. CONCLUSIONS: The beneficial effects of carvedilol on left ventricular remodelling, systolic function, and symptomatic status are not affected by concurrent treatment with amiodarone. Adverse reactions necessitating cessation of carvedilol are no more frequent in patients receiving amiodarone.